2018
DOI: 10.1111/1756-185x.13438
|View full text |Cite
|
Sign up to set email alerts
|

The impact of systemic sclerosis on health‐related quality of life assessed by SF‐36: A systematic review and meta‐analysis

Abstract: Objective The purpose of this meta‐analysis was to systematically review the literature to evaluate the impact of systemic sclerosis (SSc) on the health‐related quality of life (HRQoL) assessed by the Medical Outcomes Short‐Form‐36 questionnaire (SF‐36). Methods A systematic literature search was performed on PubMed, Web of Science and Embase until April 2017 to obtain eligible studies. Random effect model was performed to summarize the scores of each domain. Scores from the SF‐36 questionnaire were used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…A large number of studies have examined the validity of the SF-36 questionnaire, showing that the physical activity subscale discriminates between various diseases and healthy controls [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In ME/CFS patients Jason et al reported the ability of the different subscales of the SF-36 questionnaire to discriminate CFS patients from healthy controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have examined the validity of the SF-36 questionnaire, showing that the physical activity subscale discriminates between various diseases and healthy controls [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In ME/CFS patients Jason et al reported the ability of the different subscales of the SF-36 questionnaire to discriminate CFS patients from healthy controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SHAQ, SF36 and EQ-5D are frequently used to evaluate HRQoL in SSc. The SHAQ has been extensively validated in SSc [ 7 , 8 ], and is designed to measure functional ability or disability in SSc. It is quickly completed by the patients; however, by definition, it does not investigate the psychological aspect of HRQoL [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some are specific for distinct organ systems or manifestations, while others are generic and can be applied to SSc and to a broad spectrum of rheumatic and non-rheumatic diseases. Among the generic indices, the Short Form-36 (SF36) and the EuroQol Five-Dimensional descriptive system (EQ-5D) are widely used given their reliability and construct validity [ 7 , 8 ]. The SF36 is a multidimensional questionnaire evaluating both physical and mental functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Depression in patients with RA may therefore be a useful target for interventions aimed at improving subjective health and HRQoL. HRQoL is a multi‐domain and subjective concept that encompasses the impact of rheumatic disease and its treatment on a person's perception of their daily life, and it has emerged as an important outcome of interest . The Short Form‐36 questionnaire (SF‐36) is a generic instrument that has been widely used to measure physical and mental health constructs, which has been widely applied to assess the HRQoL of patients with RA .…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL is a multi-domain and subjective concept that encompasses the impact of rheumatic disease and its treatment on a person's perception of their daily life, and it has emerged as an important outcome of interest. 9 The Short Form-36 questionnaire (SF-36) is a generic instrument that has been widely used to measure physical and mental health constructs, which has been widely applied to assess the HRQoL of patients with RA. 10 It includes 8 domains: physical function (PF); role physical function (RP); body pain (BP); general health (GH); vitality (VT); social function (SF); role-emotional function (RE); mental health (MH).…”
mentioning
confidence: 99%